Pengaruh Kegiatan Intrakurikuler dan Ekstrakurikuler Keagamaanterhadap Religiusitas Siswa di SMA Negeri 6 Kota Bengkulu - Dwi Monica, Silvia; Lubis, Mawardi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
The formulation of this research is: 1) Is there an influence of religious extracurricular activities on student religiosity? 2) Is there an influence of religious extracurricular activities on student religiosity? 3) Is there an influence of extracurricular activities and religious extracurricular activities on student religiosity? This type of research is quantitative research with an ex post facto correlation approach (after the fact). This study concludes that: 1) The effect of religious intracurricular activities on student religiosity at SMA Negeri 6 Bengkulu City is 0.411 with the tcount and significance values shown in table 4.17 on page 84, tcount > ttable, namely 3.152 > 2.05183 and a significance level of 0.004 < 0.05. So in this test it shows that Ha is accepted. So that the hypothesis that says there is an influence of religious intracurricular activities on student religiosity is partially accepted. 2) The effect of religious extracurricular activities on the religiosity of students at SMA Negeri 6 Bengkulu City is 0.540 with the tcount and significance shown in table 4.17 on page 84, tcount > ttable, namely 4.142 > 2.05183 and a significance level of 0.000 <0.05. So in this test it shows that Ha is accepted. So that the hypothesis that says there is an influence of religious extracurricular activities on student religiosity is partially accepted. 3) The effect of religious extracurricular activities and religious extracurricular activities simultaneously (together) on the religiosity of students at SMA Negeri 6 Bengkulu City is 0.779 with an Fcount and significance value shown in table 4.18 on page 85. Fcount is 47.718 with a Ftable value of 3 .34 so that the value of Ftable > Fcount or 47.718 > 3.34 and a significance level of 0.000 <0.05. So in this test it shows that Ha is accepted. So that the hypothesis that says there is an influence of religious extracurricular activities and religious extracurricular activities on student religiosity is simultaneously accepted.